The Impact of the ECB's Quantitative Easing Policy on Capital Flows in the Cesee Region - Anita Angelovska – Bezhoska; Ana Mitreska; Sultanija Bojcheva – Terzijan (Journal of Central Banking Theory and Practice, 2018)
This paper attempts to empirically assess the impact of the ECB's quantitative easing policy on capital flows in the countries of the Central and South Eastern region. Given the tight trade and financial linkages of the region with the euro area, one should expect that the buoyant liquidity provided by the ECB might affect the size of the capital inflows. We test this hypothesis by employing panel estimation on a sample of 14 countries CESEE countries for the 2003-2015 period. Contrary to the expected outcome, the results reveal either negative or insignificant impact of the change in the ECB balance sheet on the different types of capital inflows. The results suggest that the magnitude of the crisis, to which the ECB responded to was immense, hence precluding any significant impact of the monetary easing on capital flows in the region. The inclusion of a dummy in the model, to control for the 2008 crisis confirms the findings from the first specification and also does not change the finding on the ECB quantitative easing impact on the capital flows. The impact of the crisis dummy on capital flows is negative and it holds for almost all types of capital inflows, except for the government debt flows, which is consistent with the countercyclical fiscal policies and rising public debt after the crisis.
Keywords: E43; F21; C33; 330; quantitative easing polices; ECB; capital flows; CESEE countries; panel estimates; mean group estimator.